Pitfalls of central clearing in the presence of systematic risk - Christian Kubitza; Loriana Pelizzon; Mila Getmansky Sherman (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2019)
Through the lens of market participants' objective to minimize counterparty risk, we investigate central clearing in derivatives markets, and its interaction with systematic risk, portfolio directionality, and loss sharing. Previous studies suggest that central clearing always reduces counterparty risk for a sufficiently large number of clearing members. We show that this is not the case - mostly because of loss sharing. Central clearing can increase counterparty risk, particularly during extreme market events, for traders with directional portfolios, and because CCPs mutualize default losses. Our results are consistent with the reluctance to clear derivative trades in the absence of a clearing obligation.
Keywords: G01; G14; G18; G28; 330; Central Clearing; Counterparty Risk; Systematic Risk; OTC markets; Derivatives; Margin